2013
DOI: 10.1111/irv.12094
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose oral interferon alpha as prophylaxis against viral respiratory illness: a double‐blind, parallel controlled trial during an influenza pandemic year

Abstract: Background and objectiveInterferon alpha (IFNα) is a known antiviral agent. A double‐blind, placebo‐controlled clinical trial was conducted investigating the use of low‐dose oral interferon alpha for preventing acute viral respiratory illnesses.MethodsTwo hundred healthy adults aged 18–75 years were enrolled and completed weekly health data questionnaires to monitor for symptoms and impact of respiratory illness. Serum samples were tested for antibodies against influenza and other common respiratory viruses.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…O'Neil et al [47] compared the efficacy of commercially available Echinacea capsules in preventing URIs symptoms compared to placebo over a period of 8 weeks during the winter months, and reported that Echinacea capsules did not significantly alter the frequency of URIs symptoms. Bennett et al [48] determined the efficacy of low dose interferon alpha (IFNα) lozenges in the prevention of URIs in healthy adults (n = 275, aged 18-75 years), based on weekly health data questionnaires. These investigators reported that lowdose oral IFN-α prophylaxis did not affect the incidence of URI, but did reduce the severity and duration of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…O'Neil et al [47] compared the efficacy of commercially available Echinacea capsules in preventing URIs symptoms compared to placebo over a period of 8 weeks during the winter months, and reported that Echinacea capsules did not significantly alter the frequency of URIs symptoms. Bennett et al [48] determined the efficacy of low dose interferon alpha (IFNα) lozenges in the prevention of URIs in healthy adults (n = 275, aged 18-75 years), based on weekly health data questionnaires. These investigators reported that lowdose oral IFN-α prophylaxis did not affect the incidence of URI, but did reduce the severity and duration of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…When given prophylactically, type I IFN reduces IAV replication and disease severity in both animals [52] and humans [53] . Therapeutic administration, however, is ineffective in animal models and may actually increase lethality despite a reduction in lung IAV titers [52] .…”
Section: The Interferon Systemmentioning
confidence: 99%
“…Importantly, exogenous IFN cannot be immunogenic; otherwise neutralizing antibody responses develop, rendering treatment ineffective [ 47 ]. In an attempt to overcome adverse side effects with current modes of IFN-α treatment, a recent clinical trial investigating administration of low-dose oral IFN-α prophylaxis was undertaken but was deemed ineffective in protection against acute respiratory illness during the 2009 influenza pandemic [ 48 ].…”
Section: Innate Interferonsmentioning
confidence: 99%